The Path of Internet Law: An Annotated Guide to Legal Landmarks - D’Angelo, Diane (2011)
The evolution of the Internet has forever changed the legal landscape. The Internet is the world’s largest marketplace, copy machine, and instrumentality for committing crimes, torts, and infringing intellectual property. Justice Holmes’s classic essay on the path of the law drew upon six centuries of case reports and statutes. In less than twenty-five years, Internet law has created new legal dilemmas and challenges in accommodating new information technologies. Part I is a brief timeline of Internet case law and statutory developments for Internet-related intellectual property (IP) law. Part II describes some of the ways in which the Internet is redirecting the path of IP in a globalized information-based economy. Our broader point is that every branch of substantive and procedural law is adapting to the digital world. Part III is the functional equivalent of a GPS for locating the latest U.S. and foreign law resources to help lawyers, policymakers, academics and law students lost in cyberspace